Measure the level of banking performance in accordance with the e-marketing and total quality management requirements - داود, فضيلة سلمان; طاهر, مجيد حميد; حميد, لمى ماجد (Journal of Economics and Administrative Sciences, 2017)
Acquires Find importance of the overall quality and e-marketing management have become important factors in evaluating the performance of banks, which are related to the life of the community intimately, so it is important that the banks applying comprehensive quality and e-marketing management requirements in order to maintain their performance and determine their level, as well as the manifest importance of research in part, practical linking the requirements of total quality management and banking performance on the one hand and between the e-marketing and performance banking on the other hand, through the provision of scientific bases that can be based on the banks in question, as it kicks off the research problem in that most of the banks in the Iraqi market not apply administration overall quality as well as e-marketing in the provision of services, as the research focused on the relationship and influence between the overall e-marketing quality management requirements in the banking performance, as was the form of a questionnaire distributed to a sample of departments, divisions and units managers in the research sample banks, numbering 42 people from the banks (Middle East Ahli, National Islamic National Bank, Bank of Kurdistan, and the Bank of Huda Astmthar), as was the use of a statistical program (program (spssv.19) in the extraction Allantij. oukd concluded from research that there is a relationship and the impact of the requirements of the overall e-marketing quality management in the banking performance .